Relationship Marketing Practices and Effects on Marketing Effectiveness: An Empirical Insight from the Hotel Industry - Mazuri Abd Ghani; Aida Othman; Nor Asmahani Ibrahim; Wan Zulqurnain Wan Ismail (International Review of Management and Marketing, 2016)
This study aims to investigate the effect of relationship marketing components (trust, bonding, shared values, communication, empathy and reciprocity) on marketing effectiveness in Malaysian star-rated hotels. The data are based on findings gathered from 65 self-administered questionnaires distributed to middle level managers of three-to five star-rated hotels in the East Coast of Peninsular Malaysia. A Partial Least Squares (PLS) approach was used to analyze the data and test the hypotheses. The results of the measurement model confirm that the six dimensions of relationship marketing possess are an adequate reliability and have internal consistency as well as convergent validity. The results of structural model show that among key components of relationship marketing, trust, bonding and shared value have positive influences on marketing effectiveness, while communication, empathy and reciprocity do not. The findings of this study provided insights to hoteliers with regard to the importance of deploying and implementing relationship marketing practices as an effort to improve marketing effectiveness performance in the hospitality sector.